2021
DOI: 10.3389/fphys.2021.674550
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Antipsychotic Lumateperone Effects on the Adrenal Gland With Possible Beneficial Effect of Quercetin Co-administration

Abstract: Schizophrenia remains one of the most chronic and highly disabling mental disorders. Lumateperone is a recent FDA-approved atypical antipsychotic drug for the treatment of schizophrenia. However, the internal FDA pathologist raised concerns regarding pigment deposition associated with degeneration in different tissue in animal studies with lumateperone treatment. The adrenal gland may be implicated in lumateperone side effects, and quercetin may have the ability to fulfill this treatment gap. To prove this hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 57 publications
1
3
0
Order By: Relevance
“…Guan et al (2021a) found that the serum levels of iron, copper, and calcium increased, while magnesium, zinc, selenium, and cobalt levels significantly reduced in CUMS rats, and quercetin restored the levels of these elements, demonstrating that it could regulate trace elements in the brain. Moreover, the beneficial effects of quercetin could also be observed in other animal models, such as guinea pigs and zebrafish (El-Haroun et al, 2021;Singh et al, 2022). These studies confirmed that quercetin exerted antidepressant effects by regulating the activity of enzymatic and non-enzymatic antioxidant systems.…”
Section: Anti-oxidationsupporting
confidence: 57%
See 2 more Smart Citations
“…Guan et al (2021a) found that the serum levels of iron, copper, and calcium increased, while magnesium, zinc, selenium, and cobalt levels significantly reduced in CUMS rats, and quercetin restored the levels of these elements, demonstrating that it could regulate trace elements in the brain. Moreover, the beneficial effects of quercetin could also be observed in other animal models, such as guinea pigs and zebrafish (El-Haroun et al, 2021;Singh et al, 2022). These studies confirmed that quercetin exerted antidepressant effects by regulating the activity of enzymatic and non-enzymatic antioxidant systems.…”
Section: Anti-oxidationsupporting
confidence: 57%
“…As a flavonol with numerous biological activities, quercetin has different pharmacological effects such as antidepression, anti-cancer, antioxidant, anti-fibrosis, and antiinflammatory (Reyes-Farias and Carrasco-Pozo, 2019;Ou et al, 2020;Alshammari et al, 2021). Many studies have suggested the protection of mature neurons in the hippocampus, improvement of HPA axis dysfunction, anti-inflammatory, and anti-oxidative stress were involved in the antidepressant effects of quercetin (Sun et al, 2007;Bicca et al, 2021;El-Haroun et al, 2021;Han et al, 2021;Li et al, 2021;Sun et al, 2021), which also encompasses hippocampal neurogenesis promotion through direct and indirect effects (Chan et al, 2018;Rahvar et al, 2018;Wang et al, 2021a;Ma et al, 2021). Hence, quercetin has multiple targets and pathways compared to other antidepressants (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As in schizophrenia, adjunctive treatment with some anti-inflammatory agents seems to alleviate mania and improve depressive symptoms ( Goldsmith et al, 2016 ; Rosenblat, 2019 ). Notably, lumateperone, an antagonist for D1, D2, D4, and serotonin receptor 2A and transporters ( Kumar et al, 2018 ), improved depressive symptoms in bipolar depression patients in the first clinical trials ( Calabrese et al, 2021 ), although it also showed potential inflammatory effects ( El-Haroun et al, 2021 ). Overall, these data suggest a relatively understudied connection between dopaminergic modulation of immune function and bipolar disorder and indicate that the combination of anti-inflammatory and dopaminergic drugs could provide more beneficial alleviation of bipolar symptomatology than individual treatment.…”
Section: Regional and Disease-specific Effects Of Dopaminementioning
confidence: 99%